2021
DOI: 10.1016/j.asoc.2021.107082
|View full text |Cite
|
Sign up to set email alerts
|

Computational Intelligence in the hospitality industry: A systematic literature review and a prospect of challenges

Abstract: This research work presents a detailed survey about Computational Intelligence (CI) applied to various Hotel and Travel Industry areas. Currently, the hospitality industry's interest in data science is growing exponentially because of their expected margin of profit growth. In order to provide precise state of the art content, this survey analyzes more than 160 research works from which a detailed categorization and taxonomy have been produced. We have studied the different approaches on the various forecastin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 166 publications
(171 reference statements)
0
3
0
Order By: Relevance
“…The first general reference on a solution to the imbalance phenomenon is the work by Chawla et al (2002), where a methodology based on the creation of synthetic samples is used to balance the dataset at hand. Regarding the literature on the treatment of imbalanced data in the tourism sector using machine learning techniques, the review paper by Guerra-Montenegro et al (2021) shows that, up to that date, only a remarkable paper was found: Li and Sun (2012) focused on firm failure prediction. In such work, nearest neighbour techniques jointly with a Support Vector Machine (SVM) approach are used to generate additional samples of the minority class.…”
Section: H1mentioning
confidence: 99%
“…The first general reference on a solution to the imbalance phenomenon is the work by Chawla et al (2002), where a methodology based on the creation of synthetic samples is used to balance the dataset at hand. Regarding the literature on the treatment of imbalanced data in the tourism sector using machine learning techniques, the review paper by Guerra-Montenegro et al (2021) shows that, up to that date, only a remarkable paper was found: Li and Sun (2012) focused on firm failure prediction. In such work, nearest neighbour techniques jointly with a Support Vector Machine (SVM) approach are used to generate additional samples of the minority class.…”
Section: H1mentioning
confidence: 99%
“…The articles ( Li et al, 2021 ; Yu, Wang & Lai, 2008 ) demonstrated that timescale decomposition is an actual efficient method that followed the “divide-and-conquer” approach. For example, the divide-and-conquer approach has been used in several fields: oil prices ( Rădulescu et al, 2020 ; Wang et al, 2018 ) foreign currency exchange rate ( Jin et al, 2021 ; Lin, Chiu & Lin, 2012 ; Wang & Luo, 2021 ), stock market trend ( Cheng & Wei, 2014 ; Na & Kim, 2021 ; Stasiak, 2020 ; Wang & Luo, 2021 ), wind speed ( Hu et al, 2021 ; Wang et al, 2014 ; Xie et al, 2021 ), electronics sales ( Chen & Lu, 2021 ; Lu & Shao, 2012 ), healthcare ( Aileni, Rodica & Valderrama, 2016 ; Dwivedi et al, 2019 ; Singh, Dwivedi & Srivastava, 2020 ), and tourism market ( Chen, Lai & Yeh, 2012 ; Guerra-Montenegro et al, 2021 ; Tang et al, 2021 ). The hybrid EMD combined with the artificial neural network(ANN) method was applied to predict the first, second, and third steps moving forward wind speed time series ( Chen et al, 2021 ; Hu et al, 2021 ; Liu et al, 2012 ; Liu, Hara & Kita, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…So far, recommendation software has been integrated with various industries, providing personalized recommendations that enhance user experiences and drive customer satisfaction [8]. The hospitality sector, specifically the hotel industry, has recognized the importance of computational intelligence, and recommender systems in particular, in delivering tailored recommendations to guests, thereby improving their overall stay [9].…”
Section: Introductionmentioning
confidence: 99%